Differential Transcriptomics Analysis of IPEC-J2 Cells Single or Coinfected With Porcine Epidemic Diarrhea Virus and Transmissible Gastroenteritis Virus - Song, Lina; Chen, Jing; Hao, Pengfei; Jiang, Yuhang; Xu, Wang; Li, Letian; Chen, Si; Gao, Zihan; Jin, Ningyi; Ren, Linzhu; Li, Chang (Frontiers in Immunology, 2022)
Porcine epidemic diarrhea (PED) and transmissible gastroenteritis (TGE) caused by porcine epidemic diarrhea virus (PEDV) and transmissible gastroenteritis virus (TGEV), are two highly contagious intestinal diseases in the swine industry worldwide, which are characterized by acute gastroenteritis, watery diarrhea, vomiting in pigs of almost all ages. Notably, co-infection of TGEV and PEDV is common in piglets with diarrhea-related diseases. However, the mechanism of disease caused by the co-infection of two viruses is still unclear. In this study, intestinal porcine epithelial cells (IPEC-J2) were single or co-infected with PEDV and/or TGEV, followed by the comparison of differential expressed genes, especially ISGs, between different groups via transcriptomics analysis and real-time qPCR. The antiviral activity of interferon-induced transmembrane protein 3 (IFITM3) on PEDV and TGEV infection was also evaluated. The results showed that differentially expressed genes (DEGs) can be detected in the cells infected with PEDV, TGEV, and PEDV+TGEV at 12, 24, and 48 hpi, and the number of DEGs was the highest at 24 hpi. The DEGs are mainly annotated to the GO terms of protein binding, immune system process, organelle part, intracellular organelle part. Furthermore, 90 ISGs were up-regulated during PEDV or TGEV infection, most of which were associated with antiviral activity, including ISG15, OASL, IFITM1, and IFITM3. Further studies showed that porcine IFITM3 can significantly inhibit PEDV and TGEV infection in porcine IPEC-J2 cells and/or monkey Vero cells, indicating that porcine IFITM3 has broad-spectrum antiviral activity and no species specificity.